The ATM and ATR kinases regulate centrosome clustering and tumor recurrence by targeting KIFC1 phosphorylation - Guangjian Fan (Nature Portfolio, 2021)
Centrosome clustering is a promising therapeutic target in cancer but how it is regulated remains unclear. Here, the authors show that in response to DNA damage, ATM/ATR stabilize the centrosome clustering regulator KIFC1 leading to increased clustering efficiency and tumour recurrence.